Semigroups and formal languages : proceedings of the International Conference, in honor of the 65th birthday of Donald B. McAlister, Centro de Álgebra da Universidade de Lisboa (CAUL), Portugal 12-15 July 2005, organised with special support from Centro Internacional de Matemática (CIM) - André, Jorge M. (World Scientific, 2007)
This festschrift volume in honour of Donald B McAlister on the occasion of his 65th birthday presents papers from leading researchers in semigroups and formal languages. The contributors cover a number of areas of current interest: from pseudovarieties and regular languages to ordered groupoids and one-relator groups, and from semigroup algebras to presentations of monoids and transformation semigroups. The papers are accessible to graduate students as well as researchers seeking new directions for future work.